Neros Stimme: die Kritik an der kaiserlichen vox/phōnē in der griechischrömischen Literatur - Schulz, Verena (Hermes, 2020)
This paper analyses discussions of Nero’s voice in texts critical of the emperor, above all the works of Tacitus, Suetonius, and Cassius Dio. It argues that criticism of Nero’s voice centres around four topics: (1) Nero’s hubristic longing for a divine revelation of his voice (which responds to the panegyrical accounts of his vox caelestis); (2) Nero’s training and care of his voice in a way that is too professional, distracts him from his imperial duties, and is still unsuccessful; (3) the caricature of Nero’s voice as female or animalistic; (4) the orator Nero’s emancipation and finding of his own voice as a harmful development.
Gesehen am 09.06.2021